Shadow-Related Concavity-Convexity Inversions Reveal a Very Basic Tolerance for Impossible Shadows. (April 2014) - Casati, Roberto
The stimuli traditionally used for demonstrating shadow-related concavity–convexity inversions reveal a very basic tolerance for impossible shadows—namely, self shadows do not induce a visual request for geometrically mandatory cast shadows.